Studi Numerik Pengaruh Rasio Ld/D terhadap Thrust dan Kecepatan Fluida pada Ducted Propeller - Muhammad Ramadhani Suryolaksono; Eqwar Saputra; Janatin Nur Aripin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
Ducted propeller is an engineered propeller drive which aimed to enhance thrust force. Many ways can be done in purpose to enhance thrust force, such as geometry variation in term of Ld/D ratio. Ld/D ratio is a ratio between duct length and duct diameter. In this research, an analysis was conducted using numerical simulation. This research used two Ld/D ratio (0.4 and 0.5) and three propeller angular velocities as the variables (1000, 3000, and 5000 rpm). The result of this research showed that higher Ld/D ratio produced higher thrust force. At 5000 rpm the thrust fore increased 26.3% on duct with Ld/D ratio of 0.5. Moreover, higher propeller angular velocity produce higher fluid velocity at the ducted propeller outlet. The highest fluid velocity reached at 5000 rpm propeler angular velocity with the value of 9.8 and 10.8 m/s.Keywords: ducted propeller; Ld/D ratio; numerical simulation; thrust force